Tantangan Implementasi Pendidikan Agama Islam di Sekolah: Studi Pustaka - Lilis Sulistiawati; Ali Mastur; Santhi pertiwi; Irwan Maulana (At-Tadris: Journal of Islamic Education, 2025)
This study aims to identify various challenges in the implementation of Islamic Religious Education (PAI) in schools, particularly in the context of formal education. This study used a literature review method by reviewing various sources such as scientific journals, books, and previous research reports. The results indicate that challenges to implementing PAI in schools include limited teacher competency, low student motivation, limited facilities and infrastructure, a lack of integration of PAI values into daily life, and the influence of a less than conducive social environment. This study recommends the need to improve teacher competency through ongoing training, strengthening character-based curricula, and synergy between schools, families, and the community in supporting religious education.